Petrogenesis of Pegmatitic Gabbros of the Koçali Ophiolite (Southeast Türkiye): Implications for Boninitic Magmatism - Sar, Abdullah; Rizeli, Mustafa Eren; Ertürk, Mehmet Ali (Gazi Üniversitesi, 2026)
Pegmatitic gabbros belonging to the Koçali ophiolite, located within the southern belt ophiolites, are situated in the Southeastern Anatolia region. In this study, whole-rock geochemistry analyses were performed on pegmatitic gabbros of the Koçali ophiolite. This study aims to contribute to the petrogenesis of pegmatitic gabbros and the tectonic evolution of the Southeastern Anatolian Orogenic Belt by evaluating new data alongside previous studies. Geochemical data demonstrate that the studied rocks are tholeiitic and mostly boninitic. Pegmatitic gabbros exhibit spoon-shaped REE patterns with high MgO content and low TiO 2 values. However, low Ti/V values support a boninitic magma origin. The high Ba/La and Ba/Th ratios of the pegmatitic gabbros show a high-pressure, low-temperature, and fluid-rich environment consistent with a forearc setting. KG-1 sample indicates a boninitic magma origin with positive ƐNd (t) (+2.9) and high 87 Sr 86 Sr values (0.706666). KG-8 sample, in contrast, shows relatively enriched characteristics and an E-MORB-like affinity. When all data are evaluated together, it has been determined that the pegmatitic gabbros formed mainly from a boninitic magma source in the forearc environment of the supra-subduction zone.
MF.24.43
Keywords: Boninite; Koçali Ophiolite; Pegmatitic Gabbro; Supra-Subduction Zone; Forearc